2021
DOI: 10.1589/jpts.33.544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cane use on walking parameters and lower limb muscle activity in adults with spastic cerebral palsy: a cross-sectional study

Abstract: Adults with cerebral palsy often use a cane as a walking aid because of their decreased gait ability. However, it is unclear whether this affects lower limb muscle activity during walking. The purpose of this study was to clarify the influence of using a cane during walking on the spatio-temporal parameters of walking, lower limb muscle activity, and lower limb muscle coactivation in adults with spastic cerebral palsy. [Participants and Methods] Eleven participants with cerebral palsy were included. The spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The COI values of the tibialis anterior and medial gastrocnemius in this study were compared to those obtained by other studies. Inoue et al reported COI values during walking with and without a cane of 11 adult patients with CP [ 30 ]. The study by Inoue et al differed from ours because it classified the gait cycle into two phases: the support phase and the swing phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COI values of the tibialis anterior and medial gastrocnemius in this study were compared to those obtained by other studies. Inoue et al reported COI values during walking with and without a cane of 11 adult patients with CP [ 30 ]. The study by Inoue et al differed from ours because it classified the gait cycle into two phases: the support phase and the swing phase.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Inoue et al differed from ours because it classified the gait cycle into two phases: the support phase and the swing phase. According to their study, the COI values of CP patients without a cane were 0.57 ± 0.09 in the stance phase and 0.46 ± 0.09 in the swing phase [ 30 ]. Our results show that the COI values on the operative side before HAL-SJ training were higher than those observed during the previous study (operative side COI in the stance phase: case 1, 0.77 ± 0.19, and case 2, 0.68 ± 0.21; operative side COI in the swing phase: case 1, 0.57 ± 0.21, and case 2, 0.54 ± 0.12).…”
Section: Discussionmentioning
confidence: 99%